2005
DOI: 10.1038/sj.bjp.0706350
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 activation results in disruption of the blood–brain barrier in the rat

Abstract: 1 We have examined the role of TRPV1 activation in disrupting the blood-brain barrier by measuring the permeability of single pial venular capillaries in anaesthetized rats. 2 Capsaicin application to the brain surface resulted in increased permeability, maximal 2.170.12 Â 10 À6 cm s À1 (mean7s.e.m.) with log EC 50 À4.570.10. Substance P methyl ester gave a similar response (maximal 2.070.07, n ¼ 6, log EC 50 À4.870.07), but the selective NK 2 agonist, b-Ala 8 -NKA 4-10 peptide, had no effect. Although CGRP de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 37 publications
2
46
0
Order By: Relevance
“…It also has been reported that TRPV1 is found in the brain on astrocytes and pericytes, which are closely associated with vasculature (Toth et al, 2005). TRPV1 receptor is active in the brain microvasculature and exerts its permeability-increasing effect via substance P (Hu et al, 2005). In the present study, local administration of RTX on C1-C2 spinal segments did not interrupt the augmentation of CBF or the reductions of CVR by cSCS.…”
Section: Role Of Trpv1supporting
confidence: 60%
“…It also has been reported that TRPV1 is found in the brain on astrocytes and pericytes, which are closely associated with vasculature (Toth et al, 2005). TRPV1 receptor is active in the brain microvasculature and exerts its permeability-increasing effect via substance P (Hu et al, 2005). In the present study, local administration of RTX on C1-C2 spinal segments did not interrupt the augmentation of CBF or the reductions of CVR by cSCS.…”
Section: Role Of Trpv1supporting
confidence: 60%
“…Broad expression patterns have fostered the view that central TRPV1 plays a role in pain processing and thermoregulation, and independent studies have suggested that PANEM cells may all express TRPV1, characterizing the BBB as a TRPV1-rich microenvironment (18,20,22). Activation of TRPV1 by application of the agonist capsaicin directly to the brain disrupts BBB integrity (23), and peripheral TRPV1 stimulation also opens the BBB and blood spinal cord barriers (BSCB) (24), supporting recent evidence that TRPV1 may modify cytokine signaling during CNS neuroinflammation and implying a disease-modifying role (25).…”
Section: Trpv1 Gates Tissue Access and Sustains Pathogenicity In Automentioning
confidence: 99%
“…This results in excessive mitochondrial Ca 2ϩ loading and subsequent mitochondrial disruption, leading to neuronal cell death (17,18). Activation of TRPV1 by treatment with CAP was found to increase glutamate release from nigral slices (19), produce hypokinesia in parallel with decreased nigrostriatal neuron activity (20,21), and disrupt the blood-brain barrier following ischemia-reperfusion (22). Several lines of evidence have implicated 12-HPETE, an endogenous TRPV1 agonist (10), in the induction of long-term depression in the hippocampus (23) and neurodegeneration in mesencephalic cultures (24).…”
mentioning
confidence: 99%